Zur Messung der Nutzung regionaler Potenziale beim Ausbau erneuerbarer Energien. Eine empirische Analyse deutscher Landkreise - Bennat, Tatjana; Broekel, Tom; Sternberg, Rolf (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
This paper answers two rarely considered questions: How well do German regions exploit their potential to produce renewable energy and which factors impact on this exploitation efficiency? By applying the new quantitative-empirical concept of exploitation efficiency, we measure the degree, to which regions have exploited their natural and socio-economic potentials of producing energy from renewable source at a specific point in time. This approach allows, with respect to wind power, solar power and biogas energy, a relative comparison of regions, monitoring their performance over time as well as the identification of best-practice regions. Applying our innovative method, we compare German districts in the time period 2000-2014. We use a robust, non-parametric efficiency analysis and validate its results by qualitative expert interviews in selected counties in Lower Saxony. The results show strong disparities in terms of the exploitation efficiency between districts and federal states. This exploitation efficiency moreover varies significantly for different types of renewable energy. We also observe specialization tendencies in this context. Our empirical results are very detailed both from a spatial and from a temporal perspective and therefore allow for drawing several conclusions for local and federal state policies. For instance, those districts (and federal states) with currently rather low exploitation efficiencies need to learn from those with high efficiencies. Such learning effects may sustainably contribute to a successful turnaround in energy policy.